2010
DOI: 10.1103/physreva.81.013631
|View full text |Cite
|
Sign up to set email alerts
|

Transport of ultracold Bose gases beyond the Gross-Pitaevskii description

Abstract: We explore atom-laser-like transport processes of ultracold Bose-condensed atomic vapors in mesoscopic waveguide structures beyond the Gross-Pitaevskii mean-field theory. Based on a microscopic description of the transport process in the presence of a coherent source that models the outcoupling from a reservoir of perfectly Bose-Einstein condensed atoms, we derive a system of coupled quantum evolution equations that describe the dynamics of a dilute condensed Bose gas in the framework of the Hartree-Fock-Bogol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 65 publications
(166 reference statements)
3
47
0
Order By: Relevance
“…A gapeless modification was proposed in [23] for homogenous Bose-condensates. Analysis of transport properties of Bose-condensates in mesoscopic waveguides was given in [24]. Bosons in random potentials were studied in [25], see also [26] for a comprehensive review containing, in particular, analysis of the HFB approximation in the nonuniform case and its generalizations.…”
Section: Introductionmentioning
confidence: 99%
“…A gapeless modification was proposed in [23] for homogenous Bose-condensates. Analysis of transport properties of Bose-condensates in mesoscopic waveguides was given in [24]. Bosons in random potentials were studied in [25], see also [26] for a comprehensive review containing, in particular, analysis of the HFB approximation in the nonuniform case and its generalizations.…”
Section: Introductionmentioning
confidence: 99%
“…However, for an increased incoming particle current the scattering solution turns permanently time-dependent, and the condensate and non-condensate densities rapidly fluctuate. As conjectured in [47], the lack of a stationary scattering solution is associated with a large fraction of non-condensed atoms, which, in turn, implies the breakdown of the Hartree-Fock-Bogoliubov theory. In other words, in order to describe this scattering behavior more thoroughly, a theoretical description is needed which overcomes the limitations of the Hartree-Fock-Bogoliubov theory, and in particular allows for a realistic description of large non-condensate fractions.…”
Section: Relation To Our Setup: Matter Wave Scattering Off a Disordermentioning
confidence: 99%
“…Recently, matter wave scattering based on the Hartree-Fock Bogoliubov theory has been suggested [46,47]. The analysis in [47] revealed that for increasing interaction strength a strong depletion of the condensate sets in, which, in turn, outreaches the regime of validity of this model. Hence, the development of a proper theoretical description far from equilibrium and capable of describing the full transition from a condensate to a non-condensate is in order.…”
Section: Diffusion and The Weak Localization Correctionmentioning
confidence: 99%
See 2 more Smart Citations